Geospatial modeling of the Birch River: Distribution of Carmine Shiner (Notropis percobromus) in Geomorphic Response Units (GRU). Issue 5 (30th October 2015) - Carr, Meghan; Watkinson, Douglas A.; Svendsen, Jon C.; Enders, Eva C.; Long, Jeffrey M.; Lindenschmidt, Karl‐Erich
Abstract : Carmine Shiner ( Notropis percobromus ) is a threatened cyprinid with a limited distribution in Canada occurring only in a few tributaries in the Winnipeg River watershed in southern Manitoba. The Geomorphic Response Unit (GRU) method was used to identify potential critical habitat of Carmine Shiner. The GRU method is a promising geospatial modeling technique that allows the identification of river reaches that exhibit similar geomorphic structure and provides a link between the hydrological regime and species habitat preference. Carmine Shiner catch data from June and July 2011, Geographic Information System (GIS), and multivariate‐derived GRUs were used to characterize possible Carmine Shiner spawning sites in the Birch River. Results indicate that immature Carmine Shiner (58%) prefer geomorphically variable reaches while mature Carmine Shiner (50%) prefer low‐sinuosity reaches punctuated by increases in slope. Identifying spatial patterns in the distribution of Carmine Shiner during spawning has the potential to increase understanding of habitat requirements and can aid in management efforts for this threatened species.